2003
DOI: 10.1002/ab.10023
|View full text |Cite
|
Sign up to set email alerts
|

Executive cognitive functioning and aggression: Is it an issue of impulsivity?

Abstract: A large body of research has documented a relation between the executive cognitive functions (ECFs) and interpersonal aggressive behavior. A predominant theory proposes that individuals with poor ECFs are more aggressive because they are unable to inhibit impulsive behaviors. However, evidence for this relationship is typically indirect. In this study, 46 healthy men and women completed measures of ECF, the Taylor Aggression Paradigm, and the Go/No-Go discrimination task, a behavioral measure of impulsivity. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
88
2
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(95 citation statements)
references
References 70 publications
(78 reference statements)
4
88
2
1
Order By: Relevance
“…Then the coders and B. Ann 5 Studies that looked at personality variables hypothesized to decrease aggressive behavior were excluded from the present analysis. These included anxiety (Bjork et al, 1997;Dengerink, 1971;Dorsky & Taylor, 1972;Wilkinson, 1985), depression (Bjork et al, 1997), empathy and perspective taking (Giancola, 2003;Perugini & Gallucci, 2001; Richardson, Hammock, Smith, Gardner, & Signo, 1984;Strayer & Roberts, 2004), executive functioning (Hoaken, Shaughnessy, & Pihl, 2003;Santor, Ingram, & Kusumakar, 2003), intelligence (Giancola & Zeichner, 1994), nonviolence (Sen, 1986), reflection (Irwin & Gross, 1995), selfconsciousness (Spivey & Prentice-Dunn, 1990), and social integration and ascendancy (Boyatzis, 1975). Also, studies that looked at individual differences hypothesized to increase aggressive behavior but that yielded only one effect size were excluded from analyses.…”
Section: Variables Coded From Each Research Reportmentioning
confidence: 99%
“…Then the coders and B. Ann 5 Studies that looked at personality variables hypothesized to decrease aggressive behavior were excluded from the present analysis. These included anxiety (Bjork et al, 1997;Dengerink, 1971;Dorsky & Taylor, 1972;Wilkinson, 1985), depression (Bjork et al, 1997), empathy and perspective taking (Giancola, 2003;Perugini & Gallucci, 2001; Richardson, Hammock, Smith, Gardner, & Signo, 1984;Strayer & Roberts, 2004), executive functioning (Hoaken, Shaughnessy, & Pihl, 2003;Santor, Ingram, & Kusumakar, 2003), intelligence (Giancola & Zeichner, 1994), nonviolence (Sen, 1986), reflection (Irwin & Gross, 1995), selfconsciousness (Spivey & Prentice-Dunn, 1990), and social integration and ascendancy (Boyatzis, 1975). Also, studies that looked at individual differences hypothesized to increase aggressive behavior but that yielded only one effect size were excluded from analyses.…”
Section: Variables Coded From Each Research Reportmentioning
confidence: 99%
“…However, researches on impulsivity as a personality trait, have frequently reported that men are more impulsive than women (Bettencourt & Millar, 1996;Waldeck & Miller, 1997), although other works have not found these relations (Hoaken, Shaughnessy, & Pihl, 2003;Smith, Waterman, & Ward, 2006). In any case, most of these studies have used questionnaires, and the correlation between objective and subjective measures of impulsivity has not yet been sufficiently established (Enticott, Ogloff, & Bradshaw, 2006;Lane, Cherek, Rhodes, Pietras, & Tcheremissine, 2003;Malle & Neubauer, 1990;Phillips & Rabbitt, 1995).…”
mentioning
confidence: 99%
“…Both the Iowa Gambling Task and the go/no-go discrimination task (see, e.g., Hoaken, Shaughnessy, & Pihl, 2003) are often used as putative measures of prefrontal circuitry, which modulates behavioral inhibition. In the Iowa Gambling Task, a high performance level is achieved by rejecting (i.e., not selecting) alternatives that produce high gains and even higher losses and instead selecting alternatives with inferior gains but smaller losses.…”
mentioning
confidence: 99%